Retrospective analysis of death due to burns in a tertiary care hospital in North Tamil Nadu - Gitanjali , Devasahayam (Journal of Indian Academy of Forensic Medicine, 2023)
Burns is a major cause of death in India and thousands die every year. Burn injuries are one of the major sources of morbidity and  mortality and is an important public health problem. Over 96% of fatal burns occur in low and middle income countries. This  retrospective study was carried out on autopsies of burn victims at the Department of Forensic Medicine & Toxicology, Government  Villupuram Medical College, Villupuramfor a period of 5 years. It was done to study the profile of these cases. Out of the 4036  autopsies done, 89 cases were due to burns. 25 (28.09%) were males and 64 (71.91%) were females. 35 (39.33%) cases were in the age  group of 21-30 years and 20 (22.47%) were in the age group 31-40 years. Most of the deaths were reported between 6 pm and midnight  (32.58%). In 91.01% of the cases, burns occurred inside the house. Deaths occurred after the victims were hospitalized in 67.42% and  32.58% deaths occurred on the spot or were declared brought dead to hospital. The cause of death was due to burns shock in 83.15%  and due to septicemia in 16.85%. Suicidal burns seem to be common among females of this region. The study clearly indicated  decreased survival period related to an increased percentage of burns. Prevention programs should be directed at behavioral and social  changes which can be easily adapted into thelifestyle of the public.
Keywords: Burns; Autopsy; Manner of death; Septicemia; Prevention programs